Handbook of South American Archaeology - Silverman, Helaine; Isbell, William; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2008)
Handbook of South American Archaeology Edited by Helaine Silverman University of Illinois at Urbana-Champaign, Urbana, IL, USA and William H. Isbell State University of New York, Binghamton, NY, USA The Handbook of South American Archaeology has been created as a major reference work for archaeologists working in South America, professors and their upper-division undergraduate and graduate students in South American archaeology courses including areal courses (Central Andes, North Andes, tropical lowlands), archaeologists working elsewhere in the world who want to learn about South American prehistory in a single volume. The contributions of this seminal handbook have been commissioned from leading local and global authorities on South America. Authors present the dynamic evolutionary processes of the ancient societies and principal geographical regions of the continent and consider issues such as environmental setting and ecological adaptations, social equality/inequality, identity formation, long-distance/intercultural interaction, religious systems and their material manifestations, ideological orientations, and political and economic organization as these developed over time. The volume is organized thematically to promote and facilitate geographical comparisons, notably between the Andes and greater Amazonia. The bibliography section of each chapter is a valuable research tool in itself for readers wishing to delve deeper into the particular topics under consideration. Of particular merit and originality is the final section dealing with the ethics and practice of archaeology in South America today with each contribution written by a local scholar. This edited work presents long-term research results while simultaneously highlighting the most exciting new research and greatest archaeological problems recently resolved or still awaiting solution. Chapters are written in accessible language and each contribution includes maps and many other figures and photographs to illustrate the text. Handbook of South American Archaeology belongs on the bookshelf of every archaeologists working or living in South American but also will be of interest to those who study larger anthropological issues - such as cultural adaptation and state formation - in the prehistoric and historic periods.
Continental Introduction -- Early Occupations Of South America -- Profiles in Pleistocene History -- Chinchorro Culture: Pioneers of the Coast of the Atacama Desert -- Early Occupations in the Southern Cone -- The Process of Sedentism in Northwestern South America -- Environment And Subsistence -- Central Andean Environments -- Plant Domestication and the Shift to Agriculture in the Andes -- Animal Domestication in South America -- High Elevation Foraging Societies -- Early Fishing Societies in Western South America -- Amazonia: The Historical Ecology of a Domesticated Landscape -- The Archaeology of Agriculture in Ancient Amazonia -- Agricultural Earthworks on the French Guiana Coast -- The Pampas and Campos of South America -- Lowland Moundbuilders -- Pre-Columbian Mound Complexes in the Upano River Valley, Lowland Ecuador -- The Archaeology of the Guianas: An Overview -- Barrancoid and Arauquinoid Mound Builders in Coastal Suriname -- Sambaqui (Shell Mound) Societies of Coastal Brazil -- Continental Variations In Non-State Complexity -- The Nonagricultural Chiefdoms of Marajó Island -- Ecology, Ceramic Chronology and Distribution, Long-term History, and Political Change in the Amazonian Floodplain -- Chiefdoms of Southwestern Colombia -- Late Pre-Hispanic Chiefdoms of Northern Colombia and the Formation of Anthropogenic Landscapes -- The Prehistory of Venezuela – Not Necessarily an Intermediate Area -- The Ecuadorian Formative -- Early Regional Polities of Coastal Ecuador -- Late Pre-Hispanic Polities of Coastal Ecuador -- Late Pre-Hispanic Chiefdoms of Highland Ecuador -- The Formative Period in the Titicaca Basin -- Paracas and Nasca: Regional Cultures on the South Coast of Peru -- Social Landscapes in Pre-Inca Northwestern Argentina -- Demographic And Cultural Expansions -- Early Cultural Complexity on the Coast of Peru -- Andean Urbanism -- The Tupi Expansion -- Life on the Move: Bioarchaeological Contributions to the Study of Migration and Diaspora Communities in the Andes -- Chavín de Huántar and Its Sphere of Influence -- States And Empires Of The Central Andes -- The Mochicas -- Wari and Tiwanaku: International Identities in the Central Andean Middle Horizon -- Between Horizons: Diverse Configurations of Society and Power in the Late Pre-Hispanic Central Andes -- The Chimú Empire -- The Inca Empire -- The Inca Khipu: Knotted-Cord Record Keeping in the Andes -- Experiencing Inca Domination in Northwestern Argentina and the Southern Andes -- Interactions -- Inter-zonal Relationships in Ecuador -- Cultural Boundaries and Crossings: Ecuador and Peru -- Chachapoyas: Cultural Development at an Andean Cloud Forest Crossroads -- The Llanos de Mojos -- Amazonian Mosaics: Identity, Interaction, and Integration in the Tropical Forest -- The Archaeology of Northern Chile -- Interaction and Social Fields in San Pedro de Atacama, Northern Chile -- Death Practices And Beliefs -- Prehistoric Funeral Practices in the Brazilian Amazon: The Maracá Urns -- Ancestor Images in the Andes -- Trophy Head-Taking and Human Sacrifice in Andean South America -- Ethics And Practice In South American Archaeology -- Archaeology, Globalization and the Nation: Appropriating the Past in Ecuador -- Cultural Heritage Management in Peru: Current and Future Challenges -- The Bennett Monolith: Archaeological Patrimony and Cultural Restitution in Bolivia -- Modernity and Politics in Colombian Archaeology -- From the Erasure to the Rewriting of Indigenous Pasts: The Troubled Life of Archaeology in Uruguay -- Public Archaeology and Management of the Brazilian Archaeological-Cultural Heritage -- Conclusion -- Conclusion.
Keywords: Archaeology; Anthropology; Archaeology; Anthropology